Penciptaan Ready To Wear dengan Teknik Sulam Payet Inspirasi Burung Mambruk Victoria - Saila Latifah Salma; Haidarsyah Dwi Albahi; M Tavip (Jurusan Seni Rupa ISBI Bandung, 2025)
The creation of this Ready to wear fashion was inspired by the Victorian Crowned Pigeon, a typical fauna of West Papua, which has blue feathers and a magnificent crown, as well as its status as a vulnerable and endangered species. The purpose of this creation is to reflect the beauty of the bird into the fashion world through the sequin embroidery technique. This research was raised based on deep concerns about the lack of application of Papuan natural aesthetics, especially the Victorian Crowned Pigeon, in a Ready to wear mode that can increase public awareness, as well as a serious threat to the decline in the bird population due to hunting and habitat destruction. Creation methods include pre-design, planning, and embodiment. The creation result is in the form of 4 Ready to wear fashions that are presented in the Bandung Fashion Runaway event on TVRI in Bandung city. This work is expected to be able to become a collection of new forms of fashion in the fashion realm as well as introduce the beauty of Indonesian fauna through Ready to wear clothing and make the Victorian Crowned Pigeon still maintain its sustainability.